A novel oxygen vacancies enriched CoNi LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline. (April 2023) - Jiang, Hao-Liang; Li, Ming-Hui; Zhao, Ling-Xi; Yan, Zhao-Xing; Xie, Meng; Lin, Jin-Ming; Zhao, Ru-Song
Abstract: Flower-like CoNi layered double oxide (LDO) was successfully synthesized and applied to activate peroxymonosulfate (PMS) to degrade tetracycline (TC). CoNi LDO was rich in oxygen vacancies (OV ) and had a high specific surface area. 30 mg/L TC was 100 % degraded in 60 min under the condition of 0.1 g/L CoNi LDO, 1.6 mM PMS, and unadjusted pH (5.45). A reaction mechanism dominated by OV was proposed in the TC removal system. Superoxide radical and singlet oxygen played major role in the reaction system, while sulfate radical and hydroxyl radical played minor role. The anti-interference ability of the CoNi LDO/PMS system to anions was relatively strong. At the same time, CoNi LDO showed high recovery efficiency. The degradation efficiency of TC was still higher than 92 % after five cycles. Through the detection of degradation intermediates, a possible degradation path was proposed. This study provided an efficient approach for TC degradation and provided a new clue for improving catalytic performance by introducing OV into the catalysts in PMS-based advanced oxidation processes systems. Graphical abstract: Unlabelled Image Highlights: Flower-like oxygen vacancies enriched CoNi LDO was used for PMS activation. Oxygen vacancies generation enhanced the catalytic efficiency of PMS by Co-Ni LDO. O 2 − and O 1 2 play a major role in CoNi LDO/PMS/TC system. Oxygen vacancies provide electrons to produce O 2 − . CoNi LDO as the catalyst showed excellent recovery efficiency.